Komitmen Organisasi Sebagai Mediator Antara Kompensasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan PT Sandang Asia Maju Abadi Semarang - Siti Hidayah; Yulia Putri Andarini; Sugeng Bowo Handayani (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to analyse organizational commitment as a mediator between compensation and work environment to employees job satisfaction. The population in this research are all employees of PT Sandang Asia Maju Abadi Semarang, which are number 265 people. Sample which is obtained with using Slovin formula in the research are as many as 159 respondents, and data that can be processed as many as 151 respondents. Sampling technique of the research is using random sampling. The method of its data analysis is using regression analysis and to analyse its mediation is using sobel, while its data processing is using the aid of SPSS program. Hypothesis testing results show that the employees organizational commitment of PT Sandang Asia Maju Abadi Semarang is positively and significantly influenced by compensation and work environment, this means that the fairer the compensation and the more comfortable the work environment, then the higher the organizational commitment. Employees job satisfaction of PT Sandang Asia Maju Abadi Semarang is positively and significantly influenced by organizational commitment, compensation, and work environment, this means that the higher the organizational commitment, the fairer the compensation, and the more comfortable the work environment, then the higher the employees job satisfaction. Testing result of the organizational commitment as mediator shows that organizational commitment can be mediator between compensation and work environment to employees job satisfaction, this means that the higher the organizational commitment, then the greater the positive effect of compensation and work environment to employees job satisfaction.